2017
DOI: 10.11609/jott.2841.9.5.10198-10207
|View full text |Cite
|
Sign up to set email alerts
|

<b>Butterfly fauna of Baghmundi, Purulia, West Bengal, India: a preliminary checklist</b>

Abstract: S h o r t C omm u n fi c a t fi o n B u t t e r ff l y ff a u n a o ff B a g hm u n d fi , P u r u l fi a , W e s t B e n g a l , I n d fi a : a p r e l fim fi n a r y c h e c k l fi s t S u p r fi y a S am a n t a , D fi p a nw fi t a D a s & S u d fi p t a M a n d a l 2 6 M a y 2 0 1 7 | V o l . 9 | N o . 5 | P p . 1 0 1 9 8 -1 0 2 0 7 1 0 . 1 1 6 0 9 / j o t . 2 8 4 1 . 9 . 5 . 1 0 1 9 8 -1 0 2 0 7 T h r e a t e n e d T a x a T h e J o u r n a l o ff T h r e a t e n e d T a x a fi s d e d fi c a t e d t o b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 7 publications
3
18
2
Order By: Relevance
“…Thirty-three species out of a total 55 species of butterflies recorded during this study were also reported in those studies (Das et al 2020;Roy et al 2022). Whereas, 22 species were observed for the first time from Cooch Behar District, which were not recorded by previous authors (Das et al 2020;Roy et al 2022) Moreover, the number of species recorded in this study is consistent with other studies regarding butterfly diversity in various locations of West Bengal with similar landscape patterns (Ghosh & Siddique 2005;Mukherjee et al 2015;Ghosh & Saha 2016;Mandal 2016;Mukherjee et al 2016;Dey et al 2017;Samanta et al 2017;Das 2018;Pahari et al 2018;Mahata et al 2020;Mukherjee & Mondal 2020). The number of species recorded from the two study sites differed slightly maybe because TA was topographically more diverse than RB and also maybe TA was more suitable to support the host plants of the recorded butterfly species.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thirty-three species out of a total 55 species of butterflies recorded during this study were also reported in those studies (Das et al 2020;Roy et al 2022). Whereas, 22 species were observed for the first time from Cooch Behar District, which were not recorded by previous authors (Das et al 2020;Roy et al 2022) Moreover, the number of species recorded in this study is consistent with other studies regarding butterfly diversity in various locations of West Bengal with similar landscape patterns (Ghosh & Siddique 2005;Mukherjee et al 2015;Ghosh & Saha 2016;Mandal 2016;Mukherjee et al 2016;Dey et al 2017;Samanta et al 2017;Das 2018;Pahari et al 2018;Mahata et al 2020;Mukherjee & Mondal 2020). The number of species recorded from the two study sites differed slightly maybe because TA was topographically more diverse than RB and also maybe TA was more suitable to support the host plants of the recorded butterfly species.…”
Section: Discussionsupporting
confidence: 91%
“…Other butterflies were carefully identified through photographs. Standard guides of entomological specialists, published literatures (Samanta et al 2017;Mukherjee & Mondal 2020), field guide books (Smetacek 2017) and some websites (Know your insects 2022; Butterflies of India 2022) were used to confirm the identification of the butterfly species. Data analysis & all the diversity indices like Shannon Weiner index, Margalef index, and evenness index were calculated using PAST software version 4.10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Butterflies were identified based on physical features with the help of field guides and reference books viz. (Kehimkar 2016;Shihan 2016;Kasambe 2018) and previously published works (viz., Sondhi et al 2013;Chowdhury 2014;Mandal 2016;Samanta et al 2017) and website on Indian butterflies (ifoundbuterfies.org). Surveys were conducted in all possible types of butterfly habitats mentioned in the study area.…”
Section: Methodsmentioning
confidence: 99%
“…In recent times several authors have reported on the diversity of butterfly population in different ecosystems under many districts of West Bengal (Chowdhury 2014;Mandal 2016;Samanta et al 2017). No comprehensive report on butterfly diversity from any part of Bankura District, however, has been reported to date.…”
Section: Platinum Open Accessmentioning
confidence: 99%